Periodontitis - A Useful Reference 2017
DOI: 10.5772/intechopen.69648
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Periodontal Tissue Remodeling during Orthodontic Tooth Movement in Mice and Men: Overview and Clinical Relevance

Abstract: Biologically active substances are expressed by cells within the periodontium in response to mechanical stimuli from orthodontic appliances. Several possible biomarkers representing biological modifications during specific phenomena as simile-inflammatory process, bone resorption and formation, periodontal ligament changes, and vascular and neural responses are proposed. Citations to potentially published trials were conducted by searching PubMed, Cochrane databases, and scientific textbooks. Additionally, han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 70 publications
1
36
0
6
Order By: Relevance
“…16 Thus, a decrease in OPG expression may probably be caused by an increase in proinflamatory cytokine triggered by orthodontic pressure, will inhibit OPG expression. 6 Results of this research also indicated the increased levels of RANKL at the pressure sites after the administration of coffee brew was larger than at the tension sites, especially on day 22. This is consistent with a research showing that the application of orthodontic force on pressure site can trigger osteoblasts to generate more RANKL expression, resulting in enhancement of osteoclastogenesis and then improvement of bone resorption.…”
Section: Discussionsupporting
confidence: 50%
“…16 Thus, a decrease in OPG expression may probably be caused by an increase in proinflamatory cytokine triggered by orthodontic pressure, will inhibit OPG expression. 6 Results of this research also indicated the increased levels of RANKL at the pressure sites after the administration of coffee brew was larger than at the tension sites, especially on day 22. This is consistent with a research showing that the application of orthodontic force on pressure site can trigger osteoblasts to generate more RANKL expression, resulting in enhancement of osteoclastogenesis and then improvement of bone resorption.…”
Section: Discussionsupporting
confidence: 50%
“…The application of Low-level laser therapy is a noninvasive alternative that has shown to be effective not only to reduce pain caused by the application of separators (Burns et al, 2001;Aihara et al, 2006;Cattaneo et al, 2009;Altan et al, 2012;Artés-Ribas et al, 2013;Bister & Meikle, 2013) in the initial stages of treatment (Chen et al, 2011), during canine retraction (Cruz et al, 2004;d'Apuzzo et al, 2013) and following activation of orthodontic final archwires (Dominguez et al, 2012) but also to reduce the overall orthodontic treatment time Domínguez-Camacho & Velásquez-Cujar, 2010;Doshi-Mehta & Bhad-Patil, 2012;Domínguez & Velásquez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this closed coil spring extending from the maxillary right first molar to both maxillary incisors. 25 Observation was conducted by means of the rats being sacrificed on day 15 before their maxillary right first and second molar were extracted together with periodontal tissue. Histological examination was then performed using hematoxylin-eosin (HE) staining technique to observe the number of osteoblasts and blood capillaries on the mesial and distal areas of periodontal ligaments.…”
mentioning
confidence: 99%